Heritable leaf traits as indicators of drought tolerance in Neltuma Alba for genetic improvement and ecological restoration - Lopez Lauenstein, Diego; Vega, Carmen Delcira; Verga, Anibal; Lascano, Hernan Ramiro; Marchelli, Paula (Springer, 2026)
Climate change-induced droughts are pressing threats to forest species, especially in semi-arid regions like the Chaco, in South America. Developing drought-adapted genetic material for Neltuma alba, a keystone species for timber and silvopastoral systems, is crucial for restoration and sustainability. Current breeding often overlooks drought adaptation, and evaluating complex physiological traits is impractical at scale. This study investigated simple, heritable leaf morphological traits as indirect selection criteria for drought tolerance in Neltuma alba. We assessed 90 individuals from three natural populations under controlled drought, monitoring senescence and survival. Ten leaf morphological traits were measured, and their narrow-sense heritability (h²) was estimated. We then analyzed associations between these traits and drought response (BLUPs for senescence and survival). Results showed that leaf size traits (e.g., leaflet length, width, area) had moderate to high heritabilities (0.40–0.69) and were significantly associated with drought tolerance. Larger leaf sizes correlated with delayed senescence but potentially reduced long-term survival, indicating a functional trade-off between growth-oriented and survival-oriented strategies. These findings demonstrate that easily measurable, heritable leaf morphological traits can serve as reliable, low-cost indicators for drought tolerance in Neltuma alba. This provides a practical tool to accelerate early selection in breeding programs and optimize genetic resource management, even using herbarium material. Tailored selection schemes, accounting for the identified trade-offs, are essential for effective restoration and sustainable management of this vital species.